The origins of Beowulf from Vergil to Wiglaf - North, Richard, 1961- (Oxford University Press, 2006)
'The Origins of Beowulf' suggests that the Anglo-Saxon poem Beowulf was composed in the winter of 826-7 as a requiem for King Beornwulf of Mercia on behalf of Wiglaf, the ealdorman who succeeded him. This study combines detective work with literary analysis to form a case that no future investigation will be able to ignore.